PENGEMBANGAN DAN PEMANFAATAN TEKNOLOGI DIGITAL DALAM PENDIDIKAN MITIGASI BENCANA UNTUK KESIAPSIAGAAN BENCANA BAGI SEKOLAH DI SUMATERA BARAT: SYSTEMATIC LITERATURE REVIEW - Maijem Simponi; Efendi Efendi; Andri Yanto; Apando Ekardo; Sefrinal Sefrinal; Okviani Syafti; Ramadhani Ramadhani (Jurnal Manajemen Pendidikan, 2026)
This article aims to analyse the development, utilisation, effectiveness and challenges of using digital technology in disaster mitigation education to improve disaster preparedness in schools. This article employs the Systematic Literature Review (SLR) method using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. The articles analysed were sourced from the Google Scholar and Scopus databases and published between 2019 and 2026. The selection process yielded 14 articles that met the inclusion criteria, which were then analysed thematically. The results of the analysis indicate that the digital technologies most widely used in disaster mitigation education are Virtual Reality (VR), Augmented Reality (AR), E-Learning, and Artificial Intelligence (AI). The use of these technologies has been shown to enhance pupils’ knowledge, risk awareness, mitigation skills, and preparedness more effectively than conventional methods. However, their implementation still faces various challenges. This analysis concludes that the integration of digital technology into disaster mitigation education has significant potential to strengthen school preparedness; therefore, the development of technology-based learning materials that are contextual, innovative and sustainable is required to support the realisation of disaster-resilient schools.